Aiming at the truth and aiming at success. (24th March 2017) - Radoilska, Lubomira
Abstract : This paper explores how the norms of belief relate to the norms of action. The discussion centres on addressing a challenge from positive illusions stating that the demands we face as believers aiming at the truth and the demands we face as agents aiming at success often pull in opposite directions. In response to this challenge, it is argued that the pursuits of aiming at the truth and aiming at success are fully compatible and mutually reinforcing. More specifically, the link between the two takes the form of a two-way connection. In addition to succeeding in virtue of getting it right, it is normatively appropriate to get it right in virtue of succeeding. This two-way connection thesis is supported by a wide scope reading of how the truth norm of belief may be satisfied. On this reading, believing p is permissible both as a result of settling the question of whether p in light of the available evidence and as a result of engaging a believer's agency in making it the case that p .